المجموعة الثانية من الأحاديث التي حكم عليها الإمام مالك في الموطأ بمخالفتها لعمل أهل المدينة ((دراسة فقهية حديثية)) (Journal of Humanitarian and Applied Sciences, 2023)
The best thing a Muslim takes care of in his life and the most helpful thing a believer spends his time on is remembering his Lord, glory be to Him, and his constant supplication to him. This is the best thing in which times are paid, and breaths are finished. It is obvious that the Noble Prophet, who advised his nation, left people after him on a right and a clear path in remembrance and supplication and other matters of their religion and their world. The authors of the hadith were honored to convey it, and they were not only satisfied with narrating the hadith, instead, they examined its validity from its defectiveness. A study singled out this research: the second group of hadiths that Imam Malik judged in Al-Muwatta as violating the work of the people of Medina, and the nature of the study required that it be divided into an introduction, four issues, and a conclusion, the first issue: the prohibition of five feedings, the second issue: the sale of cucumbers, the third issue: In weakening the value in camel theft, the fourth issue: in the chapter of blood money for error in killing, Conclusion: It included the most prominent findings of the research